STATUS MIKORIZA TUMBUHAN DI GRESSWELL NATURE RESERVE, MELBOURNE, VICTORIA, AUSTRALIA - Kramadibrata, K (Research Center for Biology-Indonesian Institute of Sciences, 2002)
A study on the mycorrhizal status of plants growing in an urban forest reserve which has still patches of remnant native vegetation was conducted in the Gresswell Nature Reserve at Bundoora, Victoria, Australia.The results showed that there were 24 families comprising 53 species.Of the 53 species,32 had AM alone, 15 had AM and ectomycorrhiza,one had ectomycorrhiza alone and five were non-mycorrhizal. There were 26 taxa AM fungi associated with plant roots i.e.,four taxa of Acaulospora, one of Entrophospora, 19 of Glomus and two of Scutellospora.